NJI 2020
DOI: 10.48029/nji.2020.cxi104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nursing Interventions in Prevention and Healing of Incontinence-Associated Dermatitis among Critical Care Patients

Abstract: Incontinence is a common problem among hospitalised patients and has been associated with multiple health complications, including incontinence-associated dermatitis (IAD) and hospitalacquired pressure ulcers (HAPUs). IAD is one of the clinical manifestations of moisture- associated skin damage (MASD). IAD is a common problem in aged patients with faecal and/or urinary incontinence. In this study it was sought to reduce the incidence of IAD among critically ill patients admitted in ICU from 5.94 rate to <2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The literature review shows that interventions in assessing IAD patients in older ICU units, early prevention, intervention management of risk factors, skin cleansing, and drying, use of skin protectants, and personnel training can be effective. 1,[23][24][25][26][27][28][29]37,39 In particular, in the context of skin cleansing, much literature lists the steps of skin cleansing in detail. 23,32 Using skin protectants to protect the skin before IAD development is effective for skin management of IAD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature review shows that interventions in assessing IAD patients in older ICU units, early prevention, intervention management of risk factors, skin cleansing, and drying, use of skin protectants, and personnel training can be effective. 1,[23][24][25][26][27][28][29]37,39 In particular, in the context of skin cleansing, much literature lists the steps of skin cleansing in detail. 23,32 Using skin protectants to protect the skin before IAD development is effective for skin management of IAD.…”
Section: Discussionmentioning
confidence: 99%
“…Skin damage is a sensitive quality indicator closely related to patient safety, posing significant challenges in clinical practice. 23 IAD patients often feel uncomfortable and experience pain, burning, itching, or tingling in the infected skin area. 2 Skin lesions associated with IAD are susceptible to infection due to impaired barrier function.…”
Section: Effects Of Iad On Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies found reduced incidence of IAD in the intervention group or 'post' groups, compared to earlier or 'pre' groups receiving routine care. 69,70 Other studies looked at factors influencing implementation of evidence-based skin care. A validation study involving 14 nurse specialists, identified 32 activities.…”
Section: Health Service Interventionsmentioning
confidence: 99%